Learning verbs more effectively through meaning congruent action animations. (October 2015) - Hald, Lea A.; van den Hurk, Marianne; Bekkering, Harold
Abstract: The current study investigates the effectiveness of learning words while displaying meaning congruent animations. We explore whether learning words with animation is sensitive to properties known to influence action understanding. We apply an embodied cognition framework and predictions from a recent theory about language and action (Action-Based Language theory, Glenberg & Gallese, 2012). The current study aims to investigate whether dynamic animations add to word learning (Experiment 1) and what the linguistic relation between the dynamic animation and the word learning is (Experiment 2). Results indicate that meaning congruent animations improved verb learning compared to meaning incongruent animations when measured by a recognition task. When measured by an active recall task, congruent animations led to better learning than static pictures. In both measures, meaning congruent animations support word learning. Experiment 2 replicates and extends this and suggests that highlighting conceptual information related to the dynamic action (such as the goal) improves word learning further. The findings are in line with Action-Based Language theory, which suggests that children are able to make better simulations of an action during learning when supported by meaning congruent animations. Highlighting conceptual information additionally supports this learning process. Highlights: We compare the effect of using animation versus pictures on word learning in children. Our results show that meaning congruent animations support word learning. Our results also illustrate the importance of the type of text paired with the animation. The results suggest an important role for animation as part of vocabulary instruction. The results also support the Action-Based Language theory of word learning.